Proposta de plataforma digital para o enfrentamento ao trabalho escravo contemporâneo no Maranhão - SANTOS, Jeyciane Elizabeth Sá (2022)
This study seeks to develop a digital platform to gather information about the history of combating slave labor in Maranhão, with the aim of facilitating communication on the subject, based on the organization of the memory of the State Commission for the Eradication of Slave Labor in Maranhão (COETRAE/MA). The online collaborative process is also considered, which arises from the insertion of information and communication technologies in the production, consumption and circulation of content. The research is anchored in a theoretical-methodological framework of authors in the field of Communication who work with the concepts of communicative practices (FRANÇA, 2004); popular communication (PERUZZO, 1998), identity and representation (HALL, 2010; 2013), networks (AGUIAR, 2017), digital platforms, from the discussion on the impacts generated by technologies in the field of communication (SANTOS, 2019); webjournalism, digital engagement (CANAVILHAS, 2014; JENKINS, 2014), journalism, memory and history in the digital age (PALACIOS, 2014); between others. Of a qualitative nature (DESLAURIERS; KÉRISIT, 2008), the investigation starts from a bibliographic review and uses a documental study to build a brief history of the fight against slave labor in Maranhão, as well as empirical research with the work of field (OLIVEIRA, 1996) with semi-structured collective and individual interviews with members of COETRAE/MA. From the elements verified in the interviews, the purpose is to build a proposal for a digital platform that brings together the materials and meets their needs.